2019
DOI: 10.1177/0004867419893426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of homeless clinic attenders with and without psychotic illness

Abstract: Aim: To compare the characteristics of clinic attenders in inner city homeless hostels with and without a diagnosed psychotic illness. Method: A cross-sectional study of homeless people attending psychiatric clinics in three inner city homeless hostels over a period of 8 years. The demographic characteristics, comorbid conditions, pathway to homelessness and pattern of homelessness of clinic attenders with a diagnosis of psychosis were compared with those who were not known to have psychotic illness. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Studies also reported an association between substance abuse and violent ( 53 ) or lethal self-harm ( 54 ). Inconsistent with other studies, ( 55 , 56 ), a coexisting psychosis was not associated with HLSMs in the current study. However, notably, the prevalence of psychosis was relatively lower in the study samples.…”
Section: Discussionsupporting
confidence: 89%
“…Studies also reported an association between substance abuse and violent ( 53 ) or lethal self-harm ( 54 ). Inconsistent with other studies, ( 55 , 56 ), a coexisting psychosis was not associated with HLSMs in the current study. However, notably, the prevalence of psychosis was relatively lower in the study samples.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, 47.5% of index admissions and 54.1% of emergency re‐admissions were for mental and behavioural disorders, which is not entirely surprising, as the cohort was drawn from attendees at psychiatric clinics and about half were diagnosed with a psychotic illness 29 . People experiencing homelessness who have a mental illness are frequent users of hospital services 30 and often require emergency admissions, largely due to crisis management of their illness 2 .…”
Section: Discussionmentioning
confidence: 63%
“…In the current study, 47.5% of index admissions and 54.1% of emergency readmissions were for mental and behavioural disorders, which is not entirely surprising, as the cohort was drawn from attendees at psychiatric clinics and about half were diagnosed with a psychotic illness. 29 People experiencing homelessness who have a mental illness are frequent users of hospital services 30 and often require emergency admissions, largely due to crisis management of their illness. 2 Issues with medication adherence to treat mental illness are likely to play a role in frequent hospital use, including prescription filling and medication storage, 4,20 which may not be possible with the unstable living conditions experienced by people who are homeless.…”
Section: Community Homeless Use Of Health Servicesmentioning
confidence: 99%
“…However, PEH with SMI have incredibly high needs and health disparities. [2][3][4][5][6][7][8][9][10] Little is known about similarities and differences in pathways to homelessness for patients with and without psychiatric illness. One study suggests that PEH with mental illness have similar pathways to homelessness as their peers without psychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unfortunately, patients experiencing homelessness (PEH) with SMI have high rates of chronic disease, increased morbidity/mortality, fragmented service use, poor primary care experiences, and social isolation. [2][3][4][5][6][7][8][9][10] Regardless of housing status, patients with SMI often struggle to navigate medical care 2,7 ; they may report dissatisfaction with access to primary care and the coordination of services received. 11 In light of perceived discrimination reported by PEH in primary care, 12,13 and the central role of primary care in addressing the mortality gap for persons with SMI, 14 there is a pressing need to identify clinic paradigms that optimize care experiences for PEH with SMI.…”
Section: Introductionmentioning
confidence: 99%